Pengembalian Kerugian Keuangan Negara Berupa Pembayaran Uang Pengganti Oleh Terpidana Korupsi - Rusdi Sanmas (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to determine the criminal law policy in the return of state financial losses in the form of replacement payments by corruption convicts and to determine the efforts made by police investigators in overcoming obstacles to the return of state financial losses in the form of replacement payments by corruption convicts. The method used in this study is a qualitative method, with a normative legal approach as the main approach and empirical legal as a supporting approach. The data sources in this study were obtained from secondary data as the main data and primary data as supporting data. Furthermore, the data were then processed using qualitative methods. The results of the study obtained information that the criminal payment of replacement money has been regulated in Law No. 31 of 1999 concerning the Eradication of Corruption as amended by Law No. 20 of 2001. The amount of replacement money payment is the same as the assets obtained from the crime of corruption. If the replacement money is not paid, the convict is sentenced to imprisonment for a period not exceeding the maximum threat of the principal sentence. Therefore, the return of state financial losses cannot be optimal. The amount of compensation for state financial losses needs to be increased, by confiscating and seizing the perpetrator's assets/wealth. The Asset Confiscation Law needs to be formed as a legal basis for confiscating assets from corruption.